The United Nations in the 1990s - Baehr, Peter R. author. aut Link
XV, 197 p.
Keywords: At a time when the UN demonstrates new vitality, this straightforward explanation of nearly a half century of the world organization's experience provides essential background. It sets out the fundamental features of the structure of the UN and traces the political developments around such topics as maintaining international peace, protecting human rights, and improving economic welfare. Its authors are longtime observers and recognized scholars. Their transatlantic collaboration provides an extra edge of objectivity.